CCL5/RANTES gene polymorphisms in Slavonic patients with myocardial infarction - Tereshchenko, Irina P; Petrkova, Jana; Voevoda, Mikhail I; Taborsky, Milos; Navratilova, Zdenka; Romaschenko, Aida G; Maksimov, Vladimir N; Mrazek, Frantisek; Petrek, Martin (Mediators of inflammation, 2011)
Coronary artery inflammation is a critical process in the pathogenesis of myocardial infarction (MI). The chemokine CCL5/RANTES (regulated upon activation, normal T cells expressed and secreted) is expressed in advanced atherosclerotic lesions. Functional polymorphisms of the RANTES gene can, therefore, be involved in the pathogenesis of coronary artery disease. We examined the association of polymorphisms in the RANTES gene with myocardial infarction in Slavonic populations of Czech and Russian origin. A total of 467 post-MI patients and 337 control subjects were genotyped for RANTES promoter G-403A (rs2107538) and intron 1.1 T/C (rs2280789) variants by PCR-SSP. Both RANTES genotypes and allele frequencies did not differ between case and control groups. Haplotype-based analysis also failed to reveal an association between MI and investigated markers. Strong linkage disequilibrium was detected between particular RANTES alleles. The data do not support an association between RANTES G-403A polymorphism and MI, as reported previously.
Keywords: senioři; běloši; Genetic Predisposition to Disease; Chemokine CCL5; Russia; genotyp; jednonukleotidový polymorfismus; Genotype; nemoci koronárních tepen; Česká republika; Rusko; Middle Aged; Promoter Regions, Genetic; mužské pohlaví; infarkt myokardu; Adult; Czech Republic; Myocardial Infarction; Coronary Artery Disease; ženské pohlaví; Humans; lidé středního věku; promotorové oblasti (genetika); White People; chemokin CCL5; dospělí; genetická predispozice k nemoci; Female; Aged; lidé; Male; Polymorphism, Single Nucleotide